2010
DOI: 10.1007/s00198-010-1399-7
|View full text |Cite
|
Sign up to set email alerts
|

Neuroaxial versus general anaesthesia in geriatric patients for hip fracture surgery: does it matter?

Abstract: The influence of the mode of anaesthesia on outcome of geriatric patients with hip fractures is a controversial issue in the medical literature. In the light of an ageing society, a conclusive answer to this question is of growing importance. The purpose of this review was to assess the effect of neuroaxial and general anaesthesia on mortality and morbidity in geriatric patients sustaining a hip fracture. Following a current literature search within the Pubmed and Cochrane database (1967-2010), 34 randomised c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
101
1
10

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 173 publications
(113 citation statements)
references
References 90 publications
1
101
1
10
Order By: Relevance
“…Meta-analyses suggest that regional anaesthesia, specifically central neuraxial anesthesia, decreases the incidence of deep venous thrombosis (DVT) and pulmonary embolism as well as the incidence of postoperative confusion, in addition to reducing the risk of postoperative pneumonia in patients who require surgical stabilization [24,25].…”
Section: Discussionmentioning
confidence: 99%
“…Meta-analyses suggest that regional anaesthesia, specifically central neuraxial anesthesia, decreases the incidence of deep venous thrombosis (DVT) and pulmonary embolism as well as the incidence of postoperative confusion, in addition to reducing the risk of postoperative pneumonia in patients who require surgical stabilization [24,25].…”
Section: Discussionmentioning
confidence: 99%
“…Meta-analyses have shown that spinal anesthesia is associated with significantly reduced early mortality, fewer incidents of deep vein thrombosis, less acute postoperative confusion, a tendency to fewer myocardial infarctions, fewer cases of pneumonia, fatal pulmonary embolism and postoperative hypoxia. In this population general anesthesia and respiratory diseases were identified as significant predictor of morbidity [31] . Partially due to the fact that patients after traumatic injury are struggling with a number of contributing complications, this patient population suffers from a significantly higher mortality risk.…”
Section: Thromboembolic Eventsmentioning
confidence: 91%
“…It remains uncertain whether general or neuraxial anaesthesia is associated with better outcomes after hip fracture surgery, although evidence currently points towards neuraxial anaesthesia as the best technique for reducing postoperative morbidity (if not necessarily mortality) [77][78][79], as reflected in professional guidance [13].…”
Section: Intra-operative Managementmentioning
confidence: 99%